KENYAMANAN TEMPAT KERJA PUSTAKAWAN: PERSPEKTIF ERGONOMI - fadmawati, endang (Pustakaloka, 2014)
Factors considered onÂ  the work areÂ  the work environment, hardware, and cooperation between the computerâs users. AnÂ  increase onÂ  productivityÂ  isÂ  aÂ  librarianÂ  purpose.Â  However,Â  workÂ  inÂ  theÂ  office (library)Â  canÂ  alsoÂ  haveÂ  anÂ  impactÂ  thatÂ  is notÂ  goodÂ  forÂ  theÂ  safetyÂ  and health librarians. So it is necessary to know how safe and well in the use of work equipment in the library in order to avoid accidents and other health problems. In short, ergonomicsÂ  is the study of human behavior related to his job.